Impact of column axial load level of the seismic behavior of concrete-filled UHPC tubular column-to-footing connections reinforced with different spiral stirrup spacing - Rajai Z. Al-Rousan; Bara’a R. Alnemrawi (Results in Engineering)
The behavior of the ultra-high-performance concrete (UHPC) filled tubular columns (CFUT) was investigated in this study using the method of nonlinear finite element analysis (NLFEA). The CFUT jacketed system is utilized in many real-world engineering applications, such as bridge piers and high-rise core columns. The seismic action performance was addressed using the combined effect of the axial and lateral loadings with enhanced column confinement provided by the presence of spiral stirrups. Different column axial levels (0 %, 25 %, 50 %, and 75 %) and spiral stirrup spacing (25 mm, 50 mm, 75 mm,100 mm) were studied using thirty-two models. Results were presented in terms of the pulling and pushing capacities, failure modes, displacement, stress distribution, load-displacement envelopes and hysteretic loops, stiffness, and energy capacities degradation. The obtained results revealed that the composite action between the CFUT column parts (UHPC tube and concrete core) efficiently contributes to the structural system capacity. The lateral stiffness and the load-carrying capacity were significantly improved by the utilization of the RC column with the UHPC jackets. In addition, deformations were also improved along with reduced drift ratios due to the role of UHPC in bridging the resulting cracks. Finally, the reduction in the spiral stirrup spacing enhances the overall cyclic performance of the structural system.